2012
DOI: 10.1111/j.1750-3841.2011.02516.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenols and Antioxidant Capacity in 10 Moroccan Pomegranate Varieties

Abstract: The cultivar per se (genotype) behaved as the most influencing factor conditioning pomegranate sugar and organic acids profiles, antioxidant activity, and total phenolics. Given the divergence observed on bioactive compounds concentrations and antioxidant activity among evaluated cultivars, the genotype factor should be considered as the most influencing factor in future breeding programs to enhance the synthesis of beneficial bioactive compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 39 publications
7
49
5
1
Order By: Relevance
“…Hydroxycinnamic acid derivatives include ferulic (31,34), caffeic (33), and p-coumaric (32,35), while hydroxybenzoic acid derivatives consist of gallic (22), vanillic (21,27,28), syringic (29,30), and protocatechuic (24,26) acids. White and Cis 127 were the cultivars with the highest number of phenolic acids derivates identified compounds, namely 14 compounds, while Mollar de Elche, CG8, and Wonderful 1 presented 13 compounds.…”
Section: Identification and Quantification Of Phytochemicals Compoundmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroxycinnamic acid derivatives include ferulic (31,34), caffeic (33), and p-coumaric (32,35), while hydroxybenzoic acid derivatives consist of gallic (22), vanillic (21,27,28), syringic (29,30), and protocatechuic (24,26) acids. White and Cis 127 were the cultivars with the highest number of phenolic acids derivates identified compounds, namely 14 compounds, while Mollar de Elche, CG8, and Wonderful 1 presented 13 compounds.…”
Section: Identification and Quantification Of Phytochemicals Compoundmentioning
confidence: 99%
“…Regarding Spanish cultivars, some works have also been made, being the cultivars studied until now the following: Mollar de Elche, Piñón Tierno de Ojós, Casta del Reino de Ojós, Borde de Albatera, Borde de Orihuela, Borde de Beniel, Valenciana and Wonderful [10][11][12][32][33][34][35][36][37]. Nevertheless, much more pomegranate cultivars are grown in Spain whose potential is not well known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a number of experiments have shown that although most pomegranate varieties have similar composition of phytochemicals, the level or amount of the phytochemicals may depend on the cultivar [70,71]. Also in guava, the antioxidant activity and phytochemical composition of P. guajava vary significantly depending on to cultivar and pulp color [6].…”
Section: Variation In Chemical Composition and Bioactivity Of Sweet Pmentioning
confidence: 99%
“…The cultivar per se (genotype) behaved as the most influencing factor conditioning pomegranate sugar, organic acid profiles, antioxidant activity and total phenolics. The genotype factor should be considered as the most influencing factor in future breeding programmes to enhance the synthesis of beneficial bioactive compounds (Pilar Legua et al, 2012).…”
Section: Introductionmentioning
confidence: 99%